Metal oxynitrides as emerging materials with photocatalytic and electronic properties. Issue 5 (17th September 2015) - Fuertes, Amparo
<x xml:space="preserve">Abstract</x> Metal oxynitrides are intensively investigated as a group of materials to expand and tune the properties of oxides showing emerging applications as photocatalysts, pigments, phosphors, dielectrics and magnetic materials.